Characterisation of the key volatile compounds of commercial Gouda cheeses and their contribution to aromas according to Chinese consumers’ preferences - Chen Chen; Tonghui Tian; Haiyan Yu; Haibin Yuan; Bei Wang; Zhiyuan Xu; Huaixiang Tian (Food Chemistry: X, 2022)
A systematic flavoromics-based analysis of samples of 12 commercially available Gouda cheeses was performed to determine their key volatile components, the contribution of these components to the aromas of the cheeses, and which aromas were preferred by a panel of Chinese consumers. The sensory analysis results show that the Chinese consumers preferred young and medium cheeses, and that sensory attributes such as ‘milk’ and ‘cream’ were the most popular. Seventy-seven aroma compounds were identified by gas chromatography–mass spectrometry, and 28 of these were determined to be aroma-active compounds by gas chromatography–olfactometry analysis and calculation of their odour activity values. Partial least-squares analysis revealed that compounds such as diacetyl and acetoin correlated with aromas preferred by the Chinese consumers, while isobutyric acid, hexanoic acid and valeric acid correlated with aromas disliked by the Chinese consumers. Finally, the flavour contribution of each aroma-active compound was validated through aroma reorganisation and omission experiments.